Developments of Contactless Width Measurement Units - Mohd Izani, Muhammad Izulfikrie (Universiti Teknologi PETRONAS, 2021)
In the process of site measurement, workers will be exposed towards potential risk and hazard especially on construction site. This potential harm can affect the safety of the workers and also the productivity of the industry. In this study, a device is developed in order to take measurement which is length and width of the object in safe manner as it will be a contactless device. A laser range finder and accelerometer sensor will be used within the device to measure the distance and angle which is required for trigonometry algorithm. Trigonometry calculation will determine the length and width of the object and the result will be displayed through the user apps. As for to determine the end points of the object, user will control the device using apps to mark the points for the calculation. The result of the calculation will be displayed through the apps as well. This project is initiated to prepare for fully automation industry in the future.